PENGARUH METODE PEMBELAJARAN MIND MAPPING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Aulya Fitri; Astuti; Zulfah; Zulhendri; Molli Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research is the low ability of students to connect concepts with each other and to apply those concepts in problem-solving, as well as to use them in various contexts. This study aims to determine the effect of the Mind Mapping learning method on students' conceptual understanding abilities. This research is experimental, using a design consisting of a PreTest-PostTest Control Group Design. The population in this study is all seventh-grade students of MTs LKMD Giti for the 2025/2026 academic year. The sample in this study involved two classes, namely class VIIa (18 students), which was the experimental class given the Mind Mapping learning method treatment on Mathematical Concept abilities, and class VIIb (18 students), which was the control class that did not receive treatment. The sampling technique used in this study was total sampling. Data collection techniques used tests, observations, and documentation. Based on the research results, the Mind Mapping learning method affects the mathematical concept comprehension ability of seventh-grade students at MTs LKMD Giti. This is evident from the results of the Independent Sample T-Test, which showed a Sig. (2-tailed) value of 0.000 < 0.05. The effect size calculation using Cohen’s d of 1.774 indicates that the impact of the Mind Mapping method is in the large category.